Dulat Syzdykbekovich Dzhumabaev. Life and scientific activity (dedicated to the 70th birthday anniversary) - Assanova, A.T.; Uteshova, R. (Bulletin of the Karaganda University. Mathematics Series, 2024)
Professor Dulat Syzdykbekovich Dzhumabaev, Doctor of Physical and Mathematical Sciences, was a prominent scientist, a well-known specialist in the field of the qualitative theory of differential and integro-differential equations, the theory of nonlinear operator equations, numerical and approximate methods for solving boundary value problems.